A Study on Work Life Balance and its Effect on Job Performance in Royal Malaysia Police at Kuching District / Mohd Zawawi Yahaya - Yahaya, Mohd Zawawi (2018)
Work Life Balance and Job Performance are closely related to one another. It is a causal and effect relationship. It has been a study of many scholars and the issue contributes to job stress aggravates from time to time. Many may not realize how job stressors influence job performance other than complaining. Work life balance can be seen in three parts namely time balance, involvement balance and satisfaction balance the independent variables of Work Life Balance comprising of Time Balance, Involvement Balance and Satisfaction Balance while dependent variable is Job Performance namely Task Performance and Contextual performance. This study examines quality of work life balance and job performance relationship in Royal Malaysia Police a case study conducted at Kuching District, Sarawak It is the greatest hope that this study can provide an insight and better understanding pertaining to Work Life Balance in thriving job performance in the future not only in the Royal Malaysia Police but in public organization in general.